Artificial intelligence in education: an analysis of Italian students - Opromolla, Antonio (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
Artificial Intelligence is now present in everyday activities; the educational sector is an example. The most substantial impact concerns the academic experience of young adults, who increasingly integrate it into their study practices. The contribution shows the preliminary results of a study involving the administration of a short survey in which female university students participated, which aimed to determine their perceptions of using Artificial Intelligence systems in their educational processes. These results indicate that although Artificial Intelligence systems are used daily by the respondents, who generally take an average positive attitude towards this topic, the functionalities used are still limited, while doubts and fears are numerous.